2016
DOI: 10.1080/15592324.2016.1249082
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine nucleotides induce changes in cytosolic pools of calcium in Arabidopsis

Abstract: NAD is a pyridine nucleotide that is involved in cell metabolism and signaling of plant growth and stress. Recently, we reported on the multifaceted nature of NAD-inducible immunity in Arabidopsis. We identified NAD as an integral regulator of multiple defense layers such as production of ROS, deposition of callose, stimulation of cell death and modulation of defense metabolism including the defense hormones SA, JA and ABA, and other defense-associated metabolites. Altogether, NAD-induced immune effects confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, NAD is mainly used to control development or to produce energy by catabolism, while NADP mediates photosynthetic energy conversion as the final electron acceptor and promotes anabolism to support plant growth (Noctor et al, 2006;Hashida et al, 2009). NAD and NADP are also key regulators of non-redox reactions in broad-spectrum defence responses (P etriacq et al, 2013), and are consumed as mediators and substrates during protein modification cascades that relay cellular signals (Ziegler, 2000;Hunt et al, 2004;Shen et al, 2015;P etriacq et al, 2016a). Importantly, manipulation of NAD biosynthesis enhances resistance to pathogens through the production of reactive oxygen species and pyridine alkaloids (P etriacq et al, 2012, 2016bMiwa et al, 2017), although enhanced NAD biosynthesis neither increases cellular NAD level nor promotes growth (Hashida et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…However, NAD is mainly used to control development or to produce energy by catabolism, while NADP mediates photosynthetic energy conversion as the final electron acceptor and promotes anabolism to support plant growth (Noctor et al, 2006;Hashida et al, 2009). NAD and NADP are also key regulators of non-redox reactions in broad-spectrum defence responses (P etriacq et al, 2013), and are consumed as mediators and substrates during protein modification cascades that relay cellular signals (Ziegler, 2000;Hunt et al, 2004;Shen et al, 2015;P etriacq et al, 2016a). Importantly, manipulation of NAD biosynthesis enhances resistance to pathogens through the production of reactive oxygen species and pyridine alkaloids (P etriacq et al, 2012, 2016bMiwa et al, 2017), although enhanced NAD biosynthesis neither increases cellular NAD level nor promotes growth (Hashida et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that Pseudomonas syringae pv. tomato PstDC3000, harboring the avirulence factor AvrRpt2, induce almost all the genes induced by NAD + [80][81][82][83][84][85].…”
Section: Extracellular Nad + As Damp Signal In the Apoplast: Plant Namentioning
confidence: 99%
“…Nicotinamide adenine dinucleotide (NAD) and its phosphorylated derivative nicotinamide adenine dinucleotide phosphate (NADP) are coenzymes of pivotal importance for a wide range of redox reactions (Barron et al ., 2000; Noctor et al ., 2006; Takahashi et al ., 2009; Gakière et al ., 2018). Besides playing a key role as an electron carrier, NAD also participates in central intracellular signaling processes by serving as substrate for several regulatory proteins (Kulkarni and Brookes, 2019; Strømland et al ., 2019), in calcium homeostasis (Guse, 2015; Pétriacq et al ., 2016a), hormonal defense regulation (Pétriacq et al ., 2016b), DNA damage repair (Briggs and Bent, 2011), and cell cycle regulation (Demarest et al ., 2019). Remarkably, recent studies have demonstrated that alterations in the levels of NAD + itself may act as a signal and affect the pools of metabolites and/or the expression of genes involved in stress tolerance (Gakière et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%